Experimental Modal Analysis of Viscoelastic Sandwich Structures - Meera-Saheb Koppanati; Sairag Lanka; Krishna Bhaskar Kalidindi; Kalyanamanohar Veeramallu (Mechanics of Advanced Composite Structures, 2025)
Experimental and numerical studies are implemented in this work to investigate the modal characteristics of three-layered viscoelastic sandwich beams and plates with a natural rubber core and distinct isotropic face layers. In this study, the material of face layers in both beams and plates is varied with uniform face thickness by keeping the core constant to maintain the constant volume. Through the use of the Impact Hammer Modal Testing technique, experimental modal analysis is carried out with SAMURAI and ME' Scope software. The beams and plates are subjected to numerical analysis using ANSYS 19.2 Mechanical APDL Software, a finite element analysis (FEA) tool to evaluate the modal characteristics. The modal characteristics including natural frequencies and mode shapes of both beams and plates are evaluated under various boundary conditions, such as Clamped-Free (C–F), Simply-Supported (S–S), Clamped–Simply Supported (C–S), and Clamped-Clamped (C–C) for beams. Other plate boundary conditions that are taken into consideration for plates in this inquiry include C-F-F-F (Cantilever), S-S-S-S (All edges simply-supported), C-F-C-F (opposite edges clamped and other edges free), and C-C-C-C (All edges clamped). Ultimately, an excellent agreement is established when the outcomes of the experimental modal analysis are compared to those from ANSYS. The research also investigates how varying face layer material densities and end conditions affect natural frequencies at constant volume.